Effects of Static, Slow and Fast Dynamic Stretching on Shoulder Ioint Proprioception in Male Volleyball Players with Shoulder Impingement Syndrome - Abdolreza Sanati; Abdolhamid Daneshjoo; Mansour Sahebozamani; Elham Hosseini (Shahid Beheshti University of Medical Sciences, 2022)
Background and Aims Shoulder impingement syndrome (SIS) can affect the proprioception and disturb the normal neuromuscular reactions that the protect the shoulder joint. There are various therapeutic strategies including stretching exercises to prevent the negative effects of SIS. This study aims to investigate the effects of static, slow and fast dynamic stretching on shoulder joint proprioception in male volleyball players with SIS.Methods Participants were 18 professional male volleyball players (Age: 26.52±1.5 years, weight: 89.72±7.02 kg, height: 196.78±6.32 cm) in Kerman, Iran suffering from SIS who were selected using purposeful and convenience sampling methods. All subjects were randomly performed one type of stretching exercises for three consecutive days at the same hour and their proprioception were measured by the Leighton flexometer and target angle reconstruction with external and internal shoulder rotations before and after stretching. The data were analyzed using repeated measures ANOVA.Results The static stretching signifcantly reduced the shoulder joint proprioception (P=0.001), while the dynamic stretching at different speeds had a significant positive effect on shoulder joint proprioception (P=0.001). There was no significant difference between the two types of slow and fast dynamic stretching (P=0.8).Conclusion It seems that dynamic stretching at different speeds has a better effect on shoulder joint proprioception than static stretching in male volleyball players with SIS.